(untitled) (Perner’s Contacts, 2010)
This article is based on a topic of support quality, collation an access during implementing ISO systems with sight to quality management system in large transport companies. The first part is about national policy of quality, the second part describre quality management system and process of implementation, in the third part I focus on two ways of implementation systems including the collation.